اتجاهات الشباب الفلسطيني نحو الشائعات أثناء العدوان الصهيوني على قطاع غزة 2014: دراسة ميدانية - وافي، أمين منصور (جامعة القاهرة - كلية الإعلام, 2016)
هدفت الدراسة إلى معرفة اتجاهات الشباب الفلسطيني نحو الشائعات أثناء العدوان الصهيوني على قطاع غزة 2014م، وهي دراسة وصفية استخدمت المنهج المسحي وأداة صحيفة استقصاء على عينة من الشباب الفلسطيني في الجامعات في قطاع، واعتمدت على نظريتي المسئولية الاجتماعية والنظرية الوظيفية لتفسير الشائعات ومن أهم النتائج التي توصلت لها، احتلت شبكات التواصل الاجتماعي المرتبة الأولى كمصدر للمعلومات للشباب الفلسطيني أثناء الأزمات، واعتبر أفراد العينة إن الشائعات سلوك عدواني ضد المجتمع والنساء أكثر الفئات انسياقا وراء الشائعات، وإن سبب انتشار الشائعات يعود إلى غياب الشفافية والمعلومات الصحيحة، وبينت الدراسة أن الشائعات السياسية جاءت في المرتبة الأولى أثناء الحرب الأخيرة على غزة 2014م، وأن اتجاه الشباب نحو الشائعات جاء سلبي وإن أكثر الشائعات انتشارا خلال الحرب الشائعات هي الشائعات الورقية التي أسقطها طائرات الاحتلال، وبينت الدراسة أن مروجي الشائعات هم العملاء والخونة في الدرجة الأولى، وحسب أفراد العينة فقد حققت الشائعات أهدافها خلال الحرب ومنها إخراج الناس من بيوتهم، وإحداث وإرباك وبلبلة على المستوى المعيشي، وبينت أن سبل العلاج والتصدي للشائعات يكمن في تزويد المجتمع بالمعلومات الصحيحة والرد على الشائعات من الجهات المختصة بسرعة. وقد توصلت الدراسة إلى أنه يوجد علاقة بين العوامل الديمغرافية وبين الشائعات من حيث مصدرها ونوعها وأهدافها، وبين أنه يوجد فروق ذات دلالة إحصائية حول اتجاهات الشباب نحو الشائعات أثناء أزمة العدوان يعزى للمتغير النوع والمستوى التعليمي ومكان السكن، بالإضافة إلى عدم وجود فروق ذات دلالة إحصائية حول اتجاهات الشباب نحو الشائعات أثناء أزمة العدوان يعزى للمتغير مكان الدراسة وكلية الدراسة.
The study aimed to know the attitudes of the Palestinian youth towards rumors during the recent Zionist aggression on Gaza Strip, 2014. The study is a descriptive one that used the survey method and the questionnaire instrument and made the survey on a sample of the Palestinian youth at universities in Gaza Strip. The study was built on the social responsibility theory and the functional theory to explain the rumors. The most important results attained by the study showed that social networks ranked as the first source of information for Palestinian youth during crisis'. The sample respondents considered rumors an aggressive behavior against society. The study showed that women were classified amongst the first categories driven behind rumors. The study indicated rumors spread rapidly because of the absence of transparency, and correct information. The study demonstrated that political rumors ranked in the first place during the recent war on Gaza Strip 2014. It also showed the attitude of youth vis-a-vis rumors came negative, and the most widespread rumors through the war were the paper rumors paper dropped by the Israeli warplanes. The study showed that the rumor mongers were collaborators and traitors in the first degree. According to the sample respondents, rumors achieved their objectives that pushed people to leave their homes and created confusion and chaos on the living standard. The study showed that means to address and rumors lies providing the society with the right information and to respond to rumors through the competent authority rapidly. The study found that there was a relationship between the demographic factors and rumors in terms of its source, type and its objectives. It also indicated that there were significant differences concerning youth attitudes towards rumors during the recent aggression due to the variable the gender, the level of education and place of residence, in addition to the lack of significant statistical differences related to Youth attitudes towards rumors during the recent aggression crisis due to variable "place" of study and college of study.
Keywords: وسائل الإعلام -- الشائعات الاعلامية -- العدوان الصهيونى -- قطاع غزة -- الشباب الفلسطينى